Implikasi Hukum Pembebasan Narapidana Koruptor dalam Kondisi Penyebaran Covid 19 Perspektif Sosiologi Hukum - Mohammad, Mohammad; Sari , Insana Meliya DCA; Hidayat , Nur; Bari , Abdul (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
Sociologically, the corruptor's behaviour is against the function of law. Law as social control, dictates people's lives in juridical aspect. As a means of social control, the law determines ideal and deviant behaviour and stipulates legal sanctions against the deviant. This paper refers to normative legal research by conducting studies on legislation and legal theory related to existing problems. Furthermore, the study results showed that releasing prisoners to prevent the transmission of COVID-19 was not the right solution and was only temporary because the main problem was not over capacity in prisons and detention centres but instead government policies that prioritized continuous prison sentences. It encourages over-capacity even when there is a COVID-19 pandemic or not. In addition, releasing prisoners also has several impacts, such as the vulnerability of prisoners to COVID-19 in the community, the difficulty in finding a living, the increased crime rate, and so on. In short, releasing prisoners to reduce the spread of COVID-19 amid crowded prisons is a temporary solution.